Changing Trends in Antibiotic Sensitivity of Urinary Tract Infections by Escherichia coli at a Tertiary Care Hospital (Journal of Monno Medical College, 2026)
Background: Urinary tract infection (UTI) is one of the most common causes of bacterial infections worldwide. Rising antibiotic resistance among urinary pathogens to commonly prescribed antibiotics has become a significant therapeutic challenge.Objective:  Our study aims to investigate the patterns of antibacterial susceptibility in E. coli among patients residing in the densely populated industrial area of Gazipur, Bangladesh.Methodology: This cross-sectional study was conducted in the Department of Microbiology at Tairunnessa Memorial Medical College, Gazipur, Bangladesh from July 2023 to January 2024. The study included 100 adult patients admitted to the Medicine Indoor Department with confirmed UTI, based on clinical symptoms, signs, supportive investigations, and urine culture results (positive or negative).Results: Urine samples were taken several times from the 100 patients. Among the 1000 urine samples analyzed, 256 tested positive for pathogenic organisms. Escherichia coli was isolated in 128(50.0%) of the positive samples, followed by Klebsiella species (28.0%,), Pseudomonas species (13.7%), Enterococcus species (5.5%) and Proteus species (2.8%). Escherichia coli exhibited the highest sensitivity to nitrofurantoin (92.5%), meropenem (92.5%), amikacin (84.6%), and gentamicin (71.8%). However, it showed resistance to commonly used antibiotics such as cefixime (78%), cefuroxime (77.5%), ciprofloxacin (62.5%) and ceftriaxone (62.5%).Conclusions: Gram-negative bacilli were identified as the primary causative agents of UTI, with Escherichia coli being the most prevalent pathogen. The most effective antibiotics were nitrofurantoin, meropenem, amikacin, and gentamicin. In contrast, frequently prescribed antibiotics like cefixime, cefuroxime, cotrimoxazole, ciprofloxacin, and ceftriaxone demonstrated high resistance rates against E. coli.Journal of Monno Medical College, June, 2025; 11(1) : 44-48